I assume the 8v is a 8x
Completing the Square
x² + 8x - 9 = 0
x² + 8x - 9 + 9 = 0 + 9
x² + 8x = 9
x² + 8x + _____ = 9 + _____
x² + 8x + 16 = 9 + 16. . .How did I get 16. 8 is divided by 2 = 4 and 4 is squared (4)² = 16
x² + 8x + 16 = 25
The middle term is + 8x the left side of the equation
find the sum of the middle term
multiply the first term 1 times the last term 16 equals 16 and factor
factors of 16 =
1 x 16
2 x 8
4 x 4. . .<=..use there factors
+ 4 + 4 equals the sum of the middle term
insert + 4x and + 4x into the Left side of the equation
x² + 8x + 16 = 25
x ² + 4x + 4x + 16 = 25
x(x + 4) + 4(x + 4) = 25
(x + 4)(x + 4) = 25
(x + 4)² = 25
(√x + 4)² = ± √25
x + 4 = ± 5
x + 4 - 4 = - 4 ± 5
x = - 4 ± 5
- - - - - - -
Solving for +
x = - 4 + 5
x = 1
- - - - - - -
Solving for -
x = - 4 - 5
x = - 9
- - - - - - s-
2007-03-28 03:42:18
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Assume x² + 8x - 9 = 0
Factorising
(x + 9).(x - 1) = 0
x = - 9,x = 1
Completing Square
(x² + 8x + 16) - 16 - 9 = 0
(x + 4)² = 25
(x + 4) = ± 5
x = -9, x = 1
Quadratic Formula
x² + 8x - 9 = 0
x = [- 8 ± â(64 + 36)] / 2
x = [- 8 ± 10] / 2
x = - 9, x = 1
2007-03-28 11:38:24
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
in fact you can see that 9 = 9*1 and 8 = 9-1 so you can write down (x+9)(x-1)
but we can complete the square
x^2 +8x -9 = (x+4)^2 - 16-9 = (x+4)^2 - 5^2
so x =5-4 =1, x = -5 -4 = -9
2007-03-28 10:12:45
·
answer #3
·
answered by hustolemyname 6
·
1⤊
0⤋
use the quadratic formula. -B (plus/minus)(square root)B(squared minus 4AC) (over) 2A...in place of A B and C put your coefficient in its place...therefore... -8plus/minus the square root of 64-36 over 2 which will give you -4.26 or -11.74....i think thats the answer...good luck...
2007-03-28 10:24:31
·
answer #4
·
answered by Sam S 1
·
0⤊
0⤋
Please retype the question accurately.
2007-03-28 10:09:35
·
answer #5
·
answered by tedfischer17 3
·
0⤊
1⤋